Deciphering Single Nucleotide Polymorphisms and Evolutionary Trends in Isolates of the Cydia pomonella granulovirus - Wennmann, Jörg T. (Viruses, 2017)
Six complete genome sequences of Cydia pomonella granulovirus (CpGV) isolates from Mexico (CpGV-M and CpGV-M1), England (CpGV-E2), Iran (CpGV-I07 and CpGV-I12), and Canada (CpGV-S) were aligned and analyzed for genetic diversity and evolutionary processes. The selected CpGV isolates represented recently identified phylogenetic lineages of CpGV, namely, the genome groups A to E. The genomes ranged from 120,816 bp to 124,269 bp. Several common differences between CpGV-M, -E2, -I07, -I12 and -S to CpGV-M1, the first sequenced and published CpGV isolate, were highlighted. Phylogenetic analysis based on the aligned genome sequences grouped CpGV-M and CpGV-I12 as the most derived lineages, followed by CpGV-E2, CpGV-S and CpGV-I07, which represent the most basal lineages. All of the genomes shared a high degree of co-linearity, with a common setup of 137 (CpGV-I07) to 142 (CpGV-M and -I12) open reading frames with no translocations. An overall trend of increasing genome size and a decrease in GC content was observed, from the most basal lineage (CpGV-I07) to the most derived (CpGV-I12). A total number of 788 positions of single nucleotide polymorphisms (SNPs) were determined and used to create a genome-wide SNP map of CpGV. Of the total amount of SNPs, 534 positions were specific for exactly one of either isolate CpGV-M, -E2, -I07, -I12 or -S, which allowed the SNP-based detection and identification of all known CpGV isolates.